Software Utilities for Data Visualization and Code Management for Genealogy Reconstruction and High Quality Graph Displayal - Navas González, F.J (Archivos de zootecnia, 2023)
In the realm of data visualization and software development, specialized tools facilitate the efficient management and presentation of complex information. This article presents six distinct software utilities designed to streamline workflows in various domains including SVG file viewing, Python script editing, correlation heatmap generation, hierarchical clustering visualization, pedigree reconstruction, and Press Q statistic calculation. Each utility is described in detail, highlighting its primary functions and user interface features. By integrating these tools into their workflows, users can enhance productivity, improve data accuracy, and achieve more sophisticated analyses and visualizations. The article aims to provide a comprehensive overview of these tools, demonstrating their applications and benefits in both data visualization and software development contexts. En el ámbito de la visualización de datos y el desarrollo de software, herramientas especializadas facilitan la gestión eficiente y la presentación de información compleja. Este artículo presenta seis utilidades de software distintas diseñadas para optimizar flujos de trabajo en diversos campos, que incluyen la visualización de archivos SVG, la edición de scripts de Python, la generación de mapas de calor de correlación, la visualización de agrupamientos jerárquicos, la reconstrucción genealógica y el cálculo de la estadística Q de Press. Cada utilidad se describe detalladamente, destacando sus funciones principales y características de la interfaz de usuario. Al integrar estas herramientas en sus flujos de trabajo, los usuarios pueden mejorar la productividad, aumentar la precisión de los datos y lograr análisis y visualizaciones más sofisticados. El artículo tiene como objetivo proporcionar una visión integral de estas herramientas, demostrando sus aplicaciones y beneficios tanto en la visualización de datos como en el desarrollo de software.